57. Jahrestagung Der Deutschen Gesellschaft Für Nuklearmedizin 2019
DOI: 10.1055/s-0039-1683475
|View full text |Cite
|
Sign up to set email alerts
|

Combined FET PET/MRI radiomics differentiates radiation injury from recurrent brain metastasis

Abstract: Background: The aim of this study was to investigate the potential of combined textural feature analysis of contrast-enhanced MRI (CE-MRI) and static O-(2-[ 18 F]fluoroethyl)-L-tyrosine (FET) PET for the differentiation between local recurrent brain metastasis and radiation injury since CE-MRI often remains inconclusive. Methods: Fifty-two patients with new or progressive contrast-enhancing brain lesions on MRI after radiotherapy (predominantly stereotactic radiosurgery) of brain metastases were additionally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…92 Combined FET PET and MRI radiomics using textural features achieved a diagnostic specificity of more than 90%. 93 • Amino acid PET is useful in distinguishing posttherapeutic reactive changes following radiotherapy from recurrent BM. Present studies consistently show high diagnostic accuracy (evidence level 2).…”
Section: Amino Acid Petmentioning
confidence: 99%
“…92 Combined FET PET and MRI radiomics using textural features achieved a diagnostic specificity of more than 90%. 93 • Amino acid PET is useful in distinguishing posttherapeutic reactive changes following radiotherapy from recurrent BM. Present studies consistently show high diagnostic accuracy (evidence level 2).…”
Section: Amino Acid Petmentioning
confidence: 99%
“…These studies using various radiolabeled amino acids including 18 F-FET consistently revealed that the sensitivity and specificity for the differentiation of treatment-related changes from BM relapse is in the range of 80-90% (24,(33)(34)(35)(36)(37)(38)(39)(40). Additonally, parameters obtained from dynamic 18 F-FET PET acquisition seem to further increase the diagnostic performance compared to static parameters alone (24,34,38).…”
Section: Discussionmentioning
confidence: 90%
“…12,31,32 The emerging field of radiomics and machine learning has shown recent promise for differentiating radiation necrosis from tumor progression. 33,34 One recent study by Peng et al found that 51 radiomic features extracted using an in-house software could be used in 66 patients with 77 confirmed lesions, to differentiate tumor progression from radiation necrosis with a sensitivity and specificity of 65.38% and 86.67%, respectively, with an area under the curve of 0.81. 34 Interestingly, our radiomics regression model showed comparable predictive performance.…”
Section: Discussionmentioning
confidence: 99%